1984
DOI: 10.2165/00003088-198409040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Considerations in Drug Therapy of Cardiac Emergencies

Abstract: In the drug therapy of cardiac emergencies, it is necessary to rapidly achieve therapeutic drug concentrations and adjust drug dose as the patient's clinical status changes. Cardiac dysfunction is often present and may alter drug pharmacokinetics. Circulatory failure causes sympathetically mediated vasoconstriction in most tissues, with relative sparing of the brain and heart due to autoregulation. Blood flow to vasoconstricted tissues is reduced, and the available cardiac output is redistributed so that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 139 publications
(32 reference statements)
0
7
0
1
Order By: Relevance
“…GFR reduction by inflammatory stimuli has been reported previously (19)(20)(21). In clinical trials, GFR reduction was reported during inflammation especially when blood flow and/or blood pressure were substantially reduced, for example, in hypodynamic septic shock associated with a lowered cardiac output, which leads to a significant reduction in the clearance of a variety of drugs (34). In previous studies, i.p.…”
Section: Discussionmentioning
confidence: 70%
“…GFR reduction by inflammatory stimuli has been reported previously (19)(20)(21). In clinical trials, GFR reduction was reported during inflammation especially when blood flow and/or blood pressure were substantially reduced, for example, in hypodynamic septic shock associated with a lowered cardiac output, which leads to a significant reduction in the clearance of a variety of drugs (34). In previous studies, i.p.…”
Section: Discussionmentioning
confidence: 70%
“…Particularly if such a technique were minimally invasive, such as positron emission tomography (PET), this might be used to examine perturbations in myocardial drug handling which probably occur during cardiac emergencies (Pentel & Benowitz 1984). Thus, an individual approach to therapy with cardioactive drugs might become possible.…”
Section: Discussionmentioning
confidence: 99%
“…Data on blood flow to the vital organs are, however, scarce. an increase in hepatic flow occurs with isoproterenol or glucagon, and a decrease with p-adrenoceptor antagonists (Pentel & Benowitz 1984). A decrease in hepatic blood flow, as measured by the clearance of indocyanine green, has been reported (Koska et al 1981).…”
Section: Technical and Physiological Aspects 0/ Cardiopulmonary Bypassmentioning
confidence: 98%